Attitudes of Nunavut Inuit toward Killer Whales (Orcinus orca) - Westdal, Kristin H.; Higdon, Jeff W.; Ferguson, Steven H. (ARCTIC, 2013)
Killer whale (Orcinus orca) sightings are increasing throughout the eastern Canadian Arctic, and residents of Nunavut are concerned about the possible impact of killer whale predation on other marine mammals that are of socio-economic and cultural importance to Inuit. We analyzed the attitudes of Inuit towards killer whales, drawing on 105 semi-directed interviews conducted in 11 eastern Nunavut communities (Kivalliq and Qikiqtaaluk regions) between 2007 and 2010. Information gathered included interviewees’ firsthand knowledge, as well as knowledge they had gained through oral history. Interviews provided data on interactions between Inuit and killer whales, physical descriptions and nature of killer whales in this region, overall opinion of interviewees with respect to killer whales, historical use of the animal, opinions regarding research on killer whales and effects of killer whales on other species, particularly the whales and seals harvested for Inuit subsistence. Interviewees described killer whales as their helpers more often than as their competitors, but also as feared and dangerous. Overall, negative opinions were more common than positive opinions, and some interviewees also had a conflicted attitude towards killer whales. More participants viewed killer whales as smart and fast than as beautiful and playful. Inuit attitudes toward killer whales did not vary significantly with sex, age, hunter status, or experience with killer whales, but did vary somewhat across regions. Inuit knowledge and perspectives play a critical role in wildlife management, especially in a changing Arctic. Conservation and management of species that are important to the Inuit subsistence harvest in Nunavut must take into consideration killer whale predation, Inuit knowledge, and Inuit views and attitudes towards killer whales. Les observations d’épaulards (Orcinus orca) augmentent dans l’est de l’Arctique canadien, et les habitants du Nunavut s’inquiètent des effets possibles de la prédation des épaulards à l’égard d’autres ...